2014
DOI: 10.1177/1355819614521408
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’, policy makers’ and patients’ views of pediatric cross-border care between Malta and the UK

Abstract: Cross-border care pathways can successfully support access to high quality specialized care that is acceptable to health professionals and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…The 13 articles analyzed revealed that health actions exist that provided for integration among countries, which took form in the model of international agreements. The data on the governmental policies for the integration of healthcare in international border regions permitted their organization in themes that address the scenarios of health integration agreements, particularly European countries, (11)(12)(13)(14)(15) Asian (16)(17)(18)(19) and South American countries. (20)(21)(22)(23) In these scenarios, the types and goals of the integration agreements could be identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 13 articles analyzed revealed that health actions exist that provided for integration among countries, which took form in the model of international agreements. The data on the governmental policies for the integration of healthcare in international border regions permitted their organization in themes that address the scenarios of health integration agreements, particularly European countries, (11)(12)(13)(14)(15) Asian (16)(17)(18)(19) and South American countries. (20)(21)(22)(23) In these scenarios, the types and goals of the integration agreements could be identified.…”
Section: Resultsmentioning
confidence: 99%
“…The research methods employed were case studies with qualitative approaches (12,(14)(15)(16)20) or simply described as qualitative. (11,13) Four studies used quantitative methods (17)(18)(19)21) and two followed the mixed method. (22,23) A synthesis of the themes addressed is displayed in chart 1.…”
Section: Resultsmentioning
confidence: 99%
“…It is based on a quota of Maltese patients who go to the UK to treat rare diseases and specialties and, in exchange, British residents who are temporarily in Malta receive free health care. (14) Managers who work in border regions serve foreign patients who seek urgency and emergency services in Brazil, and care in basic health and specialized units. In Study 2 of this review, health secretaries report that bilateral cooperation between countries could ensure comprehensive care for Brazilians and foreigners.…”
Section: Discussionmentioning
confidence: 99%
“…One of the selected studies showed how the bi-national specialized health agreement between Malta and the United Kingdom in the European Union works in an effective way. (14) In the Brazilian context, the government program reported in the studies was SIS-Fronteira, one of the solutions found by Brazil to solve the problem of the border population. It is an exclusively national program with no help from its neighboring countries and definition of the role of health managers.…”
mentioning
confidence: 99%
“…MS with systems that fit less well with EU legislation may be expected to experience larger adaptations [9,10]. MS with national health service type systems would have to undergo more significant changes in order to align their health care systems with the requirements of the crossborder care directive [11][12][13]. The impact assessment of the Commission's proposal for a directive had highlighted the fact that small MS are [8] likely to face a greater financial impact as a result of cross-border care [14].…”
Section: Introductionmentioning
confidence: 99%